Synthesis of invariant circuit angular stabilization of unmanned aircraft at the pitch angle - I. V. Rozhkov (Системный анализ и прикладная информатика, 2020)
The article considers the synthesis methods of an automatic invariant system of the pitch angle stabilization of an unmanned aerial vehicle that is based on the concept of inverse dynamics problems. The methods and results of simulation mathematical results of synthesized stabilization loop with using the Simulink of program MATLAB. The results of a comparative analysis of the dynamic characteristics of the contour of angular stabilization of an unmanned aerial vehicle by pitch angle with a PID-controller and a synthesized robust controller are presented.